Recent developments in soil fertility management of maize based systems: the role of legumes in N and P nutrition of maize in the moist savanna zone of West Africa - Vanlauwe, Bernard; Aihou, K.; Iwuafor, E.; Houngnandan, P.; Diels, J.; Manyong, Victor; Sanginga, P. (2000)
The soil fertility status of the West Africa moist savanna is poor and continues to degrade. The project on balance Nutrient Management Systems for Maize based Systems in the moist Savanna and humid forest zone of West Africa (BNMS) focuses on two hypotheses which could form the basis for the development of technologies to address the generally poor soil N and P status: (i) combining N fertilizers with organic matter may improve N-use efficiency of the former , and (ii) Interactions between low reactivity rock phosphate and the rhizosphere of legumes may improve the immediate availability of rock phosphate (RP). The research activities are targeted on the derived savanna (DS) and the northern Guinea savanna (NGS) benchmarks in southern Benin and northern Nigeria, respectively. The N and P status of the soils in selected villages in the DS and NGS benchmarks was generally poor, as on average, 80% and 65% of the soils responded to fertilizer N and P respectively. Although most of the farmers in both benchmarks use inorganic fertilizer, the applications rate are low, e.g. 40kg N/ha, on average in the NGS villages.